The transfer of patents in Imperial Germany - Carsten Burhop (Max Planck Institute for Research on Collective Goods, 2009)
We describe the transfer of patents in late 19th- and early 20th- century Germany using a new and comprehensive database containing information on about 20,000 transactions. The number of transactions shows an upward trend, in total numbers and as a share of patents in force. In total, about eight percent of patents were transferred at least once during their existence. Many transactions involved the transfer of patents with an above-average quality from individual inventors to firms and to newly-created - entrepreneurial - firms. In addition, valuable patents were transferred between firms. About two-thirds of all transfers occurred during the first three years of a patents' existence, giving the new owner potentially a long period of patent protection.
Keywords: N73; O34; 330; Economic History; Germany; pre-1913; Patents; Technology transfer